Cultivation of Bulinus (Physopsis) Globosus (Morelet) and Biomphalaria Pfeifferi Pfeifferi (Krauss), Snail Hosts of Schistosomiasis (Continued from Sterkiana No. 53) - Yung-San Liang (Hello World!, 1974)
Since laboratory cultivation of Bulinus globosus and Biomphalaria pfeifferi snails has been difficult, this study was designed to develop simpler, more efficient, more dependable and more readily reproducible culture methods; it also provides a better understanding of the ecological requirements necessary for raising these snails. (Cont.)